A Math Phobia Mitigation Model to Enhance High School Students’ Motivation, Interest, and Mathematics Learning Outcomes - Rahmadani Fitri; Rabukit Damanik; Berliani Ritonga; Husaini (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Mathematics is a fundamental subject that plays an important role in developing logical and analytical thinking skills. However, many students experience math phobia, which negatively affects their motivation, interest, and learning outcomes. This study aims to (1) describe the concept of math phobia, (2) develop a math phobia mitigation model, and (3) analyze the effect of the model on students’ mathematics learning outcomes. The study employed a Research and Development (R&D) method with a mixed-methods approach. The research subjects were high school students in Binjai City. The results indicate that math phobia is characterized by emotional anxiety, cognitive disruption, and avoidance behavior. The developed mitigation model was able to increase students’ motivation and interest in learning, as well as improve learning outcomes from an average score of 62 to 82. Therefore, the mitigation model is proven to be effective in reducing mathematics anxiety and improving student achievement.